Correction: Synthesis of well-defined α, ω-telechelic multiblock copolymers in aqueous medium: in situ generation of α, ω-diols. Issue 47 (28th November 2017) - Simula, Alexandre; Nikolaou, Vasiliki; Anastasaki, Athina; Alsubaie, Fehaid; Nurumbetov, Gabit; Wilson, Paul; Kempe, Kristian; Haddleton, David M.
Abstract : Correction for 'Synthesis of well-defined α, ω-telechelic multiblock copolymers in aqueous medium: in situ generation of α, ω-diols' by Alexandre Simula et al., Polym. Chem., 2015, 6, 2226–2233.